High resolution reflection seismic imaging of the Ullared Deformation Zone, southern Sweden - Lundberg, E.; Juhlin, Christopher (2011)
The Ullared Deformation Zone (UDZ) is one of a few structures worldwide known to contain decompressed eclogite facies rocks of Precambrian age. Given the unique nature of the Ullared eclogites, a 15 km long reflection seismic profile was acquired across the UDZ in April 2007. The principal objective of the profile was to provide geometrical information on the deformation zone at depth. The profile was acquired along a crooked line which gave us the opportunity to extract strike and dip information of reflections from the data-set using non-standard seismic techniques, including a cross-dip correction. This cross-dip correction method proved to be very useful for constraining the geometry of the reflectors at depth. The most recent (from 1997) published geological interpretation of the UDZ area was based on aeromagnetic data and the UDZ was interpreted as a shear zone, or possibly a shear zone system. The seismic data and a detailed aeromagnetic analysis support the interpretation of the UDZ as a shear zone system. Based on differences in reflectivity and geometry, the UDZ can be separated into four different units. The north-easternmost unit is the only one where eclogites have been found so far. Structures of the eclogite bearing unit are interpreted to dip approximately 20-30° towards northeast at depth. © 2011 Elsevier B.V.